The complete mitochondrial DNA genome of Gymnodiptychus dybowskii (Cypriniformes: Cyprinidae: Schizothoracinae). (1st November 2016) - Yang, Tianyan; Meng, Wei; Chen, Peng; Gao, Tianxiang
Abstract: The complete nucleotide sequence of Gymnodiptychus dybowskii mitogenome (16 677 bp) has been determined, containing 13 protein-coding genes, two ribosomal RNA genes, 22 tRNA genes, and one non-coding control region. The base composition is 28.04% A, 26.92% T, 18.94% G, 26.10% C, with an AT bias of 54.97%. The origin of light-strand replication (OL ) is found between tRNA Asn and tRNA Cys, which has the potential to fold in a step-loop secondary structure with a stem formed by 11 pairs of nucleotides and a loop of 14 nucleotides. The phylogenetic analysis indicates close relationship between genus Gymnodiptychus and Diptychus .